New definitions for good practice: Regulators as activists for urban road-transported sanitation in eastern and southern Africa - Grisaffi, Claire; Leinster, Paul; Sipuma, Reuben; Owako, Emanuel; Parker, Alison (Public Library of Science (PLoS), 2026)
This paper considers the changing role of national and local regulators scaling safe emptying and transport of faecal sludge in east and southern Africa. We aim to understand how regulators are going beyond currently defined good practice and what should be learnt for others. Established roles and characteristics for regulators were synthesised and emergent practice identified, through secondary data review and key informant interviews within leading national and local regulators. This paper identified how utilities and municipalities are required to work as local regulators of service providers, who fall outside of direct or delegated arrangements, and that this role should be formally recognised to facilitate wider change. We describe the moral courage demonstrated by regulators in attempting to engage the informal sector and scale services in the face of limited resources and capacity, incomplete rules and fragmented roles and powers. Engaging informal manual emptiers already working in low-income areas, and enabling them to work safely, is considered an important part of reaching universal access by leading regulators but is not recognised in current legal frameworks and guidance. Moral courage is an important part of building trust and voluntary compliance. It is also imperative given the public health impacts of poor sanitation on the poorest and most vulnerable, and the need to challenge deeply held stigma and prejudice. We see these leading regulators as social and environmental activists, not just actors. We conclude that the focus for the sector should be on reducing the risks faced by organisations scaling this most basic of public services. In the immediate term, local, national, regional and global leaders need to recognise the important role of the informal sector in sanitation and actively support local regulators in reaching universal access.
Keywords: 4406 Human Geography; 44 Human Society; 8.1 Organisation and delivery of services; 3.2 Interventions to alter physical and biological environmental risks; Generic health relevance; 6 Clean Water and Sanitation